STRATEGI PEMERINTAH DESA BERBASIS PEMBERDAYAAN PEREMPUAN DALAM PENINGKATAN PENDAPATAN MASYARAKAT DI UMKM - Ahmad Mustanir; Muhammad Safar Akbari; Abdul Jabbar (LPPM Universitas Abdurrab, 2023)
Community empowerment aims to improve the quality of human resources to achieve a quality standard of living through changes in people's behavior. The existence of MSMEs in each village is one of the vessels in the community empowerment process as one of the efforts to improve the welfare of village communities. Likewise in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency, the existence of the Mabbulo Sipeppa Culinary MSMEs is a hope for the surrounding community in improving their welfare. The research method used was descriptive qualitative. Data were analyzed using Nvivo 12 Plus. The strategy used by the village government based on women's empowerment to increase community income through MSMEs prioritizes policies and decision-making such as budget policies, issuing distribution permits, business licenses, and halal permits. The village government always communicates with all stakeholders to develop the community and the regional potential as a learning process for future business development.